Effects of an international tournament on heart rate variability and perceived recovery in elite water polo players - Botonis, P. G.; Smilios, I.; Platanou, T. I.; Toubekis, A. G. (The Journal of Strength and Conditioning Research, 2022)
The purpose of the study was to evaluate the effects of an international tournament participation in vagal-related heart rate variability and perceived recovery among elite water polo players. Nine elite water polo players participated in an intensified training week (pretournament) and then traveled abroad to take part in an international tournament including 3 high-competitive matches during a 4-day period. Internal workload was measured after training or competition. Morning, postwakening natural logarithm of the root mean square of successive differences (lnRMSSD) and measures of perceived recovery were obtained pretournament and daily during the tournament. Logarithm of the root mean square of successive differences was also measured 30 minutes after the completion of each match of the tournament. Logarithm of the root mean square of successive differences was suppressed after the first match (p = 0.03, d = -0.75), compared with the first morning of the tournament, rebounded the following morning (p = 0.03, d = 0.87), and remained unaltered until the third match. In the last morning of the tournament, LnRMSSD was higher compared with the first postmatch measurement (p = 0.002, d = 1.57) and tended to be higher than pretournament (p = 0.09, d = 0.81). Perceived recovery and internal workloads were lower in the tournament days compared with pretournament (p < 0.001, d = 2.0 and p < 0.001, d = 14.0, respectively). In conclusion, heart rate variability may stabilize and progressively increase by the end of a tournament, as compared with a pretournament training period, reflecting an enhanced parasympathetic reactivation may be due to the reduced training load. By contrast, perceived recovery was suppressed indicating that other factors may also influence the overall recovery of the players.